O perfil brasileiro, regional e paraibano dos sistemas de inovação e das políticas públicas - Cordeiro, Ariela Diniz (2009)
The main purpose of this is to present the characteristics of the Brazilian System of Innovation and the regional ones, from an evolutionary point of view. The institutional structure and the entire support is analyzed through information available at the Science and Technology Bureau, CNPq, FINEP and general offices and foundations which works with C&T. It was found that the interactions between companies and universities are not relevant, even though the university‟s researches are financed by public resource. Additionally, it‟s observed that the C&T public policies objectives are still defined without a significant participation of Brazil‟s provinces, except for southeast states. The State of Paraíba was the case study chosen and it revealed to be very dependent of CNPq support, but with real possibilities of developing its C&T system.